A time-course study of flavonoids in the sprouts of tartary (Fagopyrum tataricum Gaertn.) buckwheats - Kim, Sun-Ju; Sarker, Md. Zaidul Islam; Maeda, Tomoo; Suzuki, Tatsuro; Hashimoto, Naoto; Takigawa, Shigenobu; Noda, Takahiro; Matsuura-Endo, Chie; Yamauchi, Hiroaki (Elsevier Inc., 2007)
The evolution, from 1 to 10 days after germination, of flavonoid content in sprouts of tartary buckwheat (Fagopyrum tataricum Gaertn.), grown in a greenhouse under low light conditions (16 mmol m2 s1), was investigated. Chlorogenic acid and flavonoids including C-glycosylflavones (orientin, isoorientin, vitexin, isovitexin), rutin and quercetin were separated from the sprouts by HPLC and quantified with their commercial standards. Rutin content in the edible portion of the sprouts (mean 20 and 37 mg g1 DWin ‘Hokkai T 8’ and ‘Hokkai T 10’, respectively) was 3- to 31-fold greater than that in the roots or pericarp. The free radical scavenging activity of seed sprouts was assessed through the 2,2-diphenyl-1- picrylhydrazyl (DPPH) assay. From 6 to 10 days after sowing, the free radical scavenging activity in the edible portions rose significantly from 1.52 to 2.33 mmol Trolox equiv. g1 DWin ‘Hokkai T 8’ and from 1.46 to 2.09 mmol Trolox equiv. g1 DWin ‘Hokkai T 10’, but differences between ‘Hokkai T 8’ and ‘Hokkai T 10’ were not significant. As the results, the sprouts of tartary buckwheat, particularly those of ‘Hokkai T 10’ are strongly recommended as new high rutin food.